2022
DOI: 10.1038/s41467-022-28641-w
|View full text |Cite
|
Sign up to set email alerts
|

The E3 ubiquitin-protein ligase Trim31 alleviates non-alcoholic fatty liver disease by targeting Rhbdf2 in mouse hepatocytes

Abstract: Systemic metabolic syndrome significantly increases the risk of morbidity and mortality in patients with non-alcoholic fatty liver disease (NAFLD) and non-alcoholic steatohepatitis (NASH). However, no effective therapeutic strategies are available, practically because our understanding of its complicated pathogenesis is poor. Here we identify the tripartite motif-containing protein 31 (Trim31) as an endogenous inhibitor of rhomboid 5 homolog 2 (Rhbdf2), and we further determine that Trim31 directly binds to Rh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
62
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(65 citation statements)
references
References 36 publications
3
62
0
Order By: Relevance
“…The experiments showed that the number of lipid droplets in HepG2 cells treated with 25, 50, and 100 μg/ml RGW decreased significantly, indicating that one of the reasons for the improvement in steatosis of hepatocytes may be a reduction in lipid deposition. Likewise, a study demonstrated that the reduction of hepatic steatosis leads to the recovery of liver function and the call-back of parameters related to lipid metabolism ( 35 ), which also confirmed our previous experimental results.…”
Section: Discussionsupporting
confidence: 90%
“…The experiments showed that the number of lipid droplets in HepG2 cells treated with 25, 50, and 100 μg/ml RGW decreased significantly, indicating that one of the reasons for the improvement in steatosis of hepatocytes may be a reduction in lipid deposition. Likewise, a study demonstrated that the reduction of hepatic steatosis leads to the recovery of liver function and the call-back of parameters related to lipid metabolism ( 35 ), which also confirmed our previous experimental results.…”
Section: Discussionsupporting
confidence: 90%
“…Developing effective strategies for NASH management largely relies on the target of the key regulators in its pathogenic pathways. Recent studies on the interaction between genetic and environmental factors on fatty liver show that metabolic disorders can significantly amplify the effects of gene variants on NASH, from steatosis to hepatic inflammation and cirrhosis 11 , 12 , 14 , 15 . Preliminary clinical trials have indicated that NASH patients with specific gene variants respond differently to lifestyle and drug intervention 44 .…”
Section: Discussionmentioning
confidence: 99%
“…Herein, more studies on the treatment of NASH in specific gene variants are urgently required, which may be helpful to guide personalized treatment in the near future. Emerging studies have reported that gene therapy approaches are of potential for the treatments of hepatic steatosis and its related HCC 10 15 , 45 , 46 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TRIM31 not only contributes significantly to cerebral ischemic injury by promoting degradation of TIGAR 14 , but also contributes in hypertensive nephropathy by promoting degradation of MAP3K7 15 . Through targeting Rhbdf2 in mouse hepatocytes, TRIM31 also alleviates non-alcoholic fatty liver disease 16 .…”
Section: Introductionmentioning
confidence: 99%